2002
DOI: 10.1038/sj.bmt.1703362
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of EBV-associated lymphoproliferative disorders after allogeneic stem cell transplantation from matched unrelated donors due to a change of T cell depletion technique

Abstract: Summary:Here, the influence of T vs T and B cell depletion on the incidence of EBV-associated lymphoproliferative disorder (EBV-LPD) after bone marrow transplantation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…The discrepancies in PTLD occurrence between our study and previous reports 1,7,9,12 are likely a result of differences in patient populations studied, use of different T lymphocyte depletion methods and differences in diagnosing/defining PTLD. The highest occurrence of PTLD was found in the study of Meijer et al 12 (5/7, that is, 71%), in which both ex vivo-selective T lymphocyte depletion of the graft and ATG administration with conditioning were used. Chiang et al 7 used both ex vivo-selective T lymphocyte depletion of the graft and in vivo ATG given post transplant (not with conditioning), and reported the occurrence of PTLD of 6%.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The discrepancies in PTLD occurrence between our study and previous reports 1,7,9,12 are likely a result of differences in patient populations studied, use of different T lymphocyte depletion methods and differences in diagnosing/defining PTLD. The highest occurrence of PTLD was found in the study of Meijer et al 12 (5/7, that is, 71%), in which both ex vivo-selective T lymphocyte depletion of the graft and ATG administration with conditioning were used. Chiang et al 7 used both ex vivo-selective T lymphocyte depletion of the graft and in vivo ATG given post transplant (not with conditioning), and reported the occurrence of PTLD of 6%.…”
Section: Discussioncontrasting
confidence: 96%
“…1,[6][7][8][9][10][11][12] In the largest study to date, which included 26 901 allogeneic HCT recipients, the cumulative incidence of PTLD was 0.2% with no T-cell depletion, 2.8% with selective (B lymphocyte sparing) T lymphocyte depletion of grafts ex vivo and 1.7% in patients receiving ATG as in vivo T lymphocyte depletion for GvHD prophylaxis or treatment. 1 In the published studies, diagnostic criteria for PTLD and strategies for its prevention varied or were not described.…”
Section: Introductionmentioning
confidence: 99%
“…The T-cell/B-cell ratio has been reported to be associated with Epstein-Barr virus-associated lymphoproliferative disorders after bone marrow transplantation from matched unrelated donors. 15 The EBMT prospective study comparing outcomes between patients treated with rATG or hATG showed increased infectious deaths with rATG; 16 in addition, a recent Japanese study on rATG in children also showed an increased infection rate. 17 Moreover, imbalanced lymphocyte subsets of activated CD4 + (CD38 + ), double-negative T cells (CD3 + CD4 -CD8 -), and regulatory T cells in rATGtreated patients may also affect immune system functions.…”
Section: Discussionmentioning
confidence: 99%
“…Meijer et al 38 report that, by maintaining a T/B cell ratio in the graft of X0.25, the risk of EBV-LPD can be significantly reduced in matched unrelated donor BMT. The role of this in autologous stem cell transplantation must be investigated.…”
Section: Discussionmentioning
confidence: 99%